2019
DOI: 10.3390/molecules25010128
|View full text |Cite
|
Sign up to set email alerts
|

Concentration-Dependent Effects of N-3 Long-Chain Fatty Acids on Na,K-ATPase Activity in Human Endothelial Cells

Abstract: N-3 eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) seem to prevent endothelial dysfunction, a crucial step in atherogenesis, by modulating the levels of vasoactive molecules and by influencing Na,K-ATPase activity of vascular myocytes. The activity of endothelial Na,K-ATPase controls the ionic homeostasis of the neighboring cells, as well as cell function. However, controversy exists with respect to the vascular protective effect of EPA and DHA. We argue that this dispute might be due to the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
0
5
1
Order By: Relevance
“…The peptaibol AlaM decreased the membrane fluidity, as measured by DPH anisotropy, above a given concentration threshold, which coincided with the onset of ATPase activation above the basic level. While other ATPases have been described to be activated by increased membrane fluidity, we find that changes in membrane fluidity are not the main driver of PM H + -ATPase activation by AlaM. The effect on plant roots in soil is therefore dependent on the concentration of peptaibols and changes in the lipid composition of the PM of live root cells.…”
Section: Discussioncontrasting
confidence: 61%
“…The peptaibol AlaM decreased the membrane fluidity, as measured by DPH anisotropy, above a given concentration threshold, which coincided with the onset of ATPase activation above the basic level. While other ATPases have been described to be activated by increased membrane fluidity, we find that changes in membrane fluidity are not the main driver of PM H + -ATPase activation by AlaM. The effect on plant roots in soil is therefore dependent on the concentration of peptaibols and changes in the lipid composition of the PM of live root cells.…”
Section: Discussioncontrasting
confidence: 61%
“…Different concentrations may lead to opposite results [ 17 ]. It may be explained that excess EPA may lead to the inhibition of Na, K-ATPase, causing cell dysfunction [ 18 , 19 ]. All these side effects may lead to ROS production and counteract the beneficial effects.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, membrane lipid peroxidation by nonenzymatic processes will yield cytotoxic products that will alter the lipid bilayer physicochemical properties (Ayala, Muñoz, & Argüelles, 2014;Cazzola et al, 2011;Catalá, 2013;Cholewski, Tomczykowa, & Tomczyk, 2018) resulting in the reduction in the degree of membrane fluidity. These cytotoxic products especially the aldehydes in the form of malondialdehyde, will selectively react with the sulfydryl (-SH) groups of the enzyme to form adducts which bring about the enzyme inhibition and damage to biological molecules (Ayala et al, 2014;Bhattacharya, 2000;Cazzola et al, 2019;Zarkovic, Cipak, Jaganjac, Borovic, & Zarkovic, 2013). Studies by Habeck et al (2017) showed that Na + /K + -ATPase activity depends on such lipids as phospholipids especially phosphatidylserine and cholesterol that stabilize the enzyme in the transmembrane vicinity and polyunsaturated phosphatidylcholine or phosphatidylethanolamine that activates the catalytic functions of the enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, it is possible that ODZ or its metabolites may have direct effect on the structure of the enzyme itself leading to low enzyme activity. Cazzola et al (2019) also attributed reduced Na + /K + -ATPase activity to lipid peroxidation by non-enzymatic processes. The observed significant dose and duration-dependent decrease in the Na + /K + -ATPase activity in this study may according to Cazzola et al (2019) be attributed to the selective reaction of the cytotoxic products of lipid peroxidation with the thiol moiety in the enzyme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation